If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -51 = 10x + -57 Reorder the terms: -51 + 8x = 10x + -57 Reorder the terms: -51 + 8x = -57 + 10x Solving -51 + 8x = -57 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -51 + 8x + -10x = -57 + 10x + -10x Combine like terms: 8x + -10x = -2x -51 + -2x = -57 + 10x + -10x Combine like terms: 10x + -10x = 0 -51 + -2x = -57 + 0 -51 + -2x = -57 Add '51' to each side of the equation. -51 + 51 + -2x = -57 + 51 Combine like terms: -51 + 51 = 0 0 + -2x = -57 + 51 -2x = -57 + 51 Combine like terms: -57 + 51 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 6x+1-3=2x+4(1+x) | | -8m^2-8n^2=-40 | | 6(25-x)+10=-15x+242 | | -z+7z=-7z-5+4z | | b^2+5bd-14d^2= | | 0=y^3-4y | | 5(4x-4)-1=20x-21 | | b^2-4b-14=2 | | 9x-4=6x+17 | | 8-5x-5-5x=5 | | 45.8+18.3(15.1-16.1)= | | 3x+14=9x-4 | | -5x+3(x+8)=16-2x | | -(2x-1)+3x=4x-5 | | 6x+6y=o | | 3x+8+3x-2=180 | | 10s^2+5s= | | 3(t-6)+5t=4(2t+5)-13 | | 2(x-5)+3=-7 | | 3a^2-6a=3 | | (x+6)(x-4)=-16 | | 5v^2+32v+35=0 | | 2x(x-12)=40 | | 11x=180 | | x^3-5x-6=0 | | 5x^3-x^2-320x+64=0 | | 6x-45=538 | | a+6-6a=12+3a | | X=8-6y | | 7x+5y=-18 | | (4u+1)(8-u)=u | | t^2-11t+30=0 |